Efektivitas Kombinasi Insektisida Nabati Daun Sirsak (Annona muricata L.) dan Daun Sirih Hijau (Piper betle) terhadap Mortalitas Ulat Grayak (Spodoptera litura F.) - Wira Guna Siswaatmadja; Albertus Sudirman; Dedy Supriyatdi; Mirodi Syofian (Universitas Sebelas Maret, 2021)
Armyworm (Spodoptera litura) is a polyphagous pest because it has a diverse host range. Armyworm is an important pest because it can cause crop failure if not controlled. One way to control it is by applying botanical insecticides. Some plants that have the potential to be used as vegetable pesticides include soursop leaf (Annona muricata L.) and green betel leaf (Piper betle L.). This study aimed to examine the effect of the combination of soursop leaf extract (Annona muricata L.) and green betel leaf extract (Piper betle L.) on the mortality of Spodoptera litura F and to obtain the best concentration of the combination of soursop leaf extract (Annona muricata L.). and vegetable insecticide green betel leaf (Piper betle L.) in the control of armyworm (Spodoptera litura F). The design used was a completely randomized design (CRD) which consisted of 7 treatments with 4 replications so that 28 experimental units were obtained. Vegetable insecticides combined with betel leaf and soursop leaf extract have the potential to control S. litura F. with the best concentration in controlling S. litura is a concentration of 60% based on armyworm mortality and killing speed of S. litura F.